Lost in thought the hidden pleasures of an intellectual life - Hitz, Zena, 1973- (Princeton University Press, 2020)
"In an overloaded, superficial, technological world, in which almost everything and everybody are judged by their usefulness, where can we turn for escape, lasting pleasure, contemplation, or connection to others? While many forms of leisure meet these needs, Zena Hitz writes, few experiences are so fulfilling as the inner life, whether that of a bookworm, an amateur astronomer, a birdwatcher, or someone who takes a deep interest in one of countless other subjects. Drawing on inspiring examples, from Socrates and Augustine to Malcolm X and Elena Ferrante, and from films to Hitz's own experiences as someone who walked away from elite university life in search of greater fulfillment, Lost in Thought is a passionate and timely reminder that a rich life is a life rich in thought. Today, when even the humanities are often defended only for their economic or political usefulness, Hitz says our intellectual lives are valuable not despite but because of their practical uselessness. And while anyone can have an intellectual life, she encourages academics in particular to get back in touch with the desire to learn for its own sake, and calls on universities to return to the person-to-person transmission of the habits of mind and heart that bring out the best in us. Reminding us of who we once were and who we might become, Lost in Thought is a moving account of why renewing our inner lives is fundamental to preserving our humanity"--